2021
DOI: 10.1021/acsami.1c00002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Design of Nitrogen-Doped Well-Defined Microporous Carbon Spheres for Selective Adsorption and Electrocatalysis

Abstract: Nitrogen-doped porous carbon spheres have attracted great interest in diversified fields owing to their unique physical and chemical properties. However, the synthesis of nitrogen-doped porous carbon spheres with hierarchical superstructures and refined micropore structures is still a challenge. Herein, we develop a molecular-scale silica templating strategy to prepare nitrogen-doped microporous carbon spheres (MCSSs) with high porosity and a well-defined micropore structure. Octa­(aminophenyl) polyhedral olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Because of pyridine N, which is bonded with two carbon atoms and is positioned at the edges of the N-doped carbon structure, it stimulates higher disorders in the resulting carbon products. Besides, the graphite N bonded with three carbon atoms in the N-doped carbon structure improves the stability and conductivity of the N-doped carbon product. ,, Here, the attained N species percentages are listed in Table S4. In Table S4, the pyridine N concentrations increase up to 0.2 g of loading and then decrease in 0.3 g of loading, whereas the graphite N concentration decreases up to 0.2 g of loading and then increases in 0.3 g of loading.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of pyridine N, which is bonded with two carbon atoms and is positioned at the edges of the N-doped carbon structure, it stimulates higher disorders in the resulting carbon products. Besides, the graphite N bonded with three carbon atoms in the N-doped carbon structure improves the stability and conductivity of the N-doped carbon product. ,, Here, the attained N species percentages are listed in Table S4. In Table S4, the pyridine N concentrations increase up to 0.2 g of loading and then decrease in 0.3 g of loading, whereas the graphite N concentration decreases up to 0.2 g of loading and then increases in 0.3 g of loading.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the graphite N bonded with three carbon atoms in the N-doped carbon structure improves the stability and conductivity of the N-doped carbon product. 34,49,53 Here, the attained N species percentages are listed in Table S4. In Table S4, the pyridine N concentrations increase up to 0.2 g of loading and then decrease in 0.3 g of loading, whereas the graphite N From these observations, we concluded that the 0.2 g of loading with a single-step addition of precursors is highly appropriate for promoting the higher concentrations of pyridine N and Co 3+ active centers and its Co 3+ /Co 2+ ratio, which may promote the sensing analysis of dopamine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical adsorption accounts for the majority of the adsorption in micropores in the type I isotherm. Due to the larger pore volume, adsorption has not taken place in macropores, and adsorbate is tightly attached to the micropores (Koyuncu and Kul 2020;Chen et al 2021;Gong et al 2022). The adsorption and desorption isotherms of CB-PAC loaded with pollutants were displayed in Fig.…”
Section: Bet Surface Area Pore Properties Ftir Spectra and Sem-eds Im...mentioning
confidence: 99%
“…Over the past decades, various carbonaceous materials with different pore structures have been explored for adsorption applications. Typically, microporous carbon with a large surface area can effectively capture small molecules with a size of less than 1 nm in all three dimensions since they can easily diffuse and be adsorbed in the micropores (<2 nm) of activated carbons (ACs). In contrast, mesoporous carbon with sufficient transportation channels exhibits an advantage for adsorbing larger molecules with a size exceeding 1.5 nm in one dimension at least. , In any case, the adsorption/desorption behaviors of petroleum hydrocarbons are dominated by interfacial interactions, such as hydrophobic interaction and van der Waals force.…”
Section: Introductionmentioning
confidence: 99%